Temporomandibular joint ankylosis - An anesthesiologist’s nightmare: Case series - Priyanka Bansal; Nidhi Sultania; Amrish Bhagol (Asian Journal of Medical Sciences, 2024)
Temporomandibular joint (TMJ) ankylosis is defined as bony or fibrous adhesion of the anatomic joint components accompanied by a limitation in opening the mouth. Airway management is a grueling task and has confronted anesthesiologists ever since. The challenge is even more exaggerated when it is a pediatric patient. We present a case series of five pediatric patients with TMJ ankylosis with age 7 years or less, who were posted for its corrective surgery. Although all patients belonged to the pediatric age group, the challenges faced and techniques employed to overcome them were different partly because of different age groups and partly the nature of the airway, with tailoring of each technique accordingly. Pediatric airway management is no less than waging a war as all necessary skills and expertise are put to the test. It combines fortuity with skills. We have to be prepared for the worst in any unforeseen scenario.